Lower limb coordinative structure in human walking - Wang, X.; O'Dwyer, N.; Halakiand, M.; Smith, R. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Human movement engages many body segments which are highly coupled. These couplings, known as synergies, have been widely investigated using principal components analysis (PCA). A primary limitation of the correlation matrices underlying PCA is that they do not account for phase differences or frequency-dependent variations in amplitude ratio between signals, yet such properties are widespread in relations between signals in the sensorimotor system. Coherence derived from dynamic linear systems analyses was introduced here to PCA applied to lower limb movements during normal walking. The results showed that one component could account for over 90% of the total variance in 26 joint angles. The findings confirm that the coordinative structure of walking is very low dimensional, comprising only a single degree of freedom.